A Simple and Sensitive Paper-Based Bipolar Electrochemiluminescence Biosensor for Detection of Oxidase-Substrate Biomarkers in Serum. Issue 9 (8th June 2018) - Wang, Dan; Liu, Cuiling; Liang, Yi; Su, Yan; Shang, Qiuping; Zhang, Chunsun
Abstract : Nowadays, the bipolar electrochemiluminescence (BP-ECL) is basically performed in complicated and expensive microfluidic devices, which may limit its wide applications. Here, a paper-based BP-ECL biosensor using "U"-shaped bipolar electrode (BPE) is developed for detection of oxidase-substrate biomarkers in human serum samples, with no need for complicated and expensive microfluidic technologies and peripheral apparatuses. The BP-ECL paper chips (PCs) can be well fabricated by two screen-printing processes: wax-screen-printing for on-paper hydrophilic and hydrophobic patterns, and carbon ink-screen-printing for BPEs and driving electrodes on wax-patterned paper. A low-cost and portable CCD is used to detect ECL signals from the luminol-H2 O2 reaction at the BPE anodic pole. Under optimized conditions, the paper-based BP-ECL biosensor can measure the concentrations of H2 O2, with a linear range of 5–10000 μM and a detection limit of 0.424 μM. Importantly, the biosensor is capable of achieving a linear range of 10–5000 μM for choline, lactate or cholesterol; and the respectively corresponding detection limits are 0.573 μM, 3.132 μM and 7.418 μM. Moreover, it has an acceptable detection range, sensitivity, stability and selectivity. Finally, the developed method is successfully applied for determination of choline, lactate or cholesterol in human serum.